2007
DOI: 10.1016/j.brainres.2007.06.052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of relative hypoglycemia on LTP and NADH imaging in rat hippocampal slices

Abstract: Cognitive and neuronal impairment in diabetes may be associated with iatrogenic hypoglycemia, particularly at low serum glucose levels (< 3 mM). To evaluate cellular impairment, we assessed acute hippocampal slice functioning during decreased ambient glucose, by monitoring evoked field excitatory post-synaptic potentials (fEPSP), and slice nicotinamide adenine dinucleotide (NADH) fluorescence. The effects of lowered glucose levels (60 min) were analyzed by examining the induction and maintenance of long-term p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Exposure to 2.5 mM glucose buffer resulted in an acute suppression of fEPSP amplitudes in all 4 age groups (Fig. 1B and C), but evoked potentials were partially maintained (Sadgrove et al, 2007). Hippocampal slices of rats from different age groups showed a similar reduction in fEPSP amplitude after 40 minutes of 2.5 mM glucose (about 80%, Fig.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Exposure to 2.5 mM glucose buffer resulted in an acute suppression of fEPSP amplitudes in all 4 age groups (Fig. 1B and C), but evoked potentials were partially maintained (Sadgrove et al, 2007). Hippocampal slices of rats from different age groups showed a similar reduction in fEPSP amplitude after 40 minutes of 2.5 mM glucose (about 80%, Fig.…”
Section: Resultsmentioning
confidence: 92%
“…During the low-glucose condition with intact oxygen availability, the NAD + /NADH redox ratio increased significantly, because of oxidation of available mitochondrial NADH to NAD + in the electron transport chain and limited substrate availability for NADH regeneration (Bryan and Jobsis, 1986; Sadgrove et al, 2007). Interestingly, we have found that the shift of NAD + /NADH toward oxidation was similar in slices of young and aging rats despite the lower oxygen utilization in aging rats compared with younger rats during moderate glucose deprivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transverse hippocampal slices (400 μm) were prepared from male rats as previously described (Galeffi et al, 2007, Sadgrove et al, 2007) and were kept in oxygenated (95 % O 2 /5% CO 2 ) ACSF (in mM: NaCl 124, KCl 3.0, NaH 2 PO 4 1.25, NaHCO 3 24, CaCl 2 2.0, MgSO 4 2.0, and dextrose 10, pH 7.4) at room temperature (22°C) for 1 hr for recovery. The slices were then transferred to oxygenated ACSF with and without 10 mM pyruvate (with changes in NaCl concentration to maintain osmolality) and incubated at 32°C for 2 - 6 hr.…”
Section: Hippocampal Slice Preparationmentioning
confidence: 99%
“…The reasons for this difference in regional cellular survival in the hippocampus are not well understood. Functionally, in vitro hypoglycemic experiments showed that the CA1 region is susceptible to synaptic failure (Abdelmalik et al, 2007;Crepel et al, 1992;Fan et al, 1988;Sadgrove et al, 2007), an effect exacerbated by the presence of seizures (Abdelmalik et al, 2007).…”
Section: Introductionmentioning
confidence: 99%